The Terminographical Process: Phases and Dimensions - Remígio, Ana (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
A proposal for segmentation and characterisation of the terminographical process, based on Gouadec’s model for translation, is presented in this paper. It comes as a result of a systematisation and comparative analysis of the various existing characterisations of the terminographical process, in an attempt – that has proven to be unfruitful – to identify the one, or a combination of different ones, which would meet the specific needs to build a resource targeted at a non-specialist public. The terminographical process is thus organised in three phases (pre-terminography, terminography, and post-terminography), and comprises three dimensions of analysis (conceptual, communicative, and textual). Broadly speaking, in pre-terminography, a preparatory piece of research is carried out (special subject field familiarisation, communicative contexts identification, and building of specialized corpora), a step which is essential to the next phase (terminography), in which a terminological database is built and populated. The last phase (post-terminography) comprises efforts aimed at the industrial application of the resource, as well as underscoring the need for its continual update. This methodology also takes into account the three dimensions of terms (conceptual, communicative and textual) which are applied and adopted in the process of termbase creation itself.